Working and Liking It - Germann, Richard; Diane Blumens and Peter Arnold (New York Fawcett Columbine, 1984)
Working and Linking It is, in a sense, an owners manual for your job. Any job. After reading this book, youll be able to repair and rebuild your job. Youll also be able to transform it into a much better one and to maintain it at that level.
Keywords: Economics